Joule-Thomson Expansion of the Quasitopological Black Holes - Mirza, Behrouz; Naeimipour, Fatemeh; Tavakoli, Masoumeh (Frontiers in Physics, 2021)
In this paper, we investigate the thermal stability and Joule-Thomson expansion of some new quasitopological black hole solutions. We first study the higher-dimensional static quasitopological black hole solutions in the presence of Born-Infeld, exponential, and logarithmic nonlinear electrodynamics. The stable regions of these solutions are independent of the types of the nonlinear electrodynamics. The solutions with horizons relating to the positive constant curvature, k=+1, have a larger region in thermal stability, if we choose positive quasitopological coefficients, μi>0. We also review the power Maxwell quasitopological black hole. We then obtain the five-dimensional Yang-Mills quasitopological black hole solution and compare it with the quasitopological Maxwell solution. For large values of the electric charge, q, and the Yang-Mills charge, e, we showed that the stable range of the Maxwell quasitopological black hole is larger than the Yang-Mills one. This is while thermal stability for small charges has the same behavior for these black holes. Thereafter, we obtain the thermodynamic quantities for these solutions and then study the Joule-Thomson expansion. We consider the temperature changes in an isenthalpic process during this expansion. The obtained results show that the inversion curves can divide the isenthalpic ones into two parts in the inversion pressure, Pi. For P<Pi, a cooling phenomenon with positive slope happens in T−P diagram, while there is a heating process with a negative slope for P>Pi. As the values of the nonlinear parameter, β, the electric and Yang-Mills charges decrease, the temperature goes to zero with a small slope and so the heating phenomena happens slowly.